Collaborative risk assessment in secure and forensic mental health settings in the UK. Issue 5 (19th August 2020) - Markham, Sarah
Abstract : Collaborative risk assessment and management have been recommended in health policy for over a decade. We consider the nature and need for collaborative risk assessment and management between patients and clinicians in secure and forensic mental health settings in the context of shared decision making and personalised care in the UK. We examine the extent to which policy and recent initiatives have influenced the embedding of such practice in services through consideration of the evidence provided by research and the Commissioning for Quality and Innovation framework, and conclude that there is a need for further improvement.